Neonatal Tetanus: Risk Factors and Prognosis - Rachma F. Boedjang (Indonesian Pediatric Society, 1995)
Neonatal tetanus (NT) remains a common cause of morbidity among neonates in Indonesia. A retrospective study was made on 83 cases on NT seen in Cipto Mangunkusumo Hospital, Jakarta over the period of 1991 -1993. The purpose of this study was to know the factors which might contributed to NT. The number of cases on NT admitted per year was almost the same; 91.6%-of cases were residents inside Jakarta and came from low socioeconomic level with low educational level. Almost 3/4 of cases were delivered by traditional birth attendants who cut the umbilical cord with uncleaned instruments or dressed it with herbal mixtures, ashes, etc. Non'e of the mothers had had tetanus immunization when they were pregnant The ratio of male to female was 1.24 : 1. All cases presented the symptoms within the first 14 days of life,Â mostly at 5-8 days of life. The overall mortality was 63.8%. The most frequently found complications were omphalitis (36%) and sepsis (24%). It is concluded that low socioeconomic level, low educational level, absence of tetanus immunization during pregnancy and poor umbilical cord dressing may contribute to the development of NT.